Patterns and drivers of diatom diversity and abundance in the global ocean - Juan J. Pierella Karlusich; Karen Cosnier; Lucie Zinger; Nicolas Henry; Charlotte Nef; Guillaume Bernard; Eleonora Scalco; Etienne Dvorak; Tara Oceans Coordinators; Fabio Rocha Jimenez Vieira; Erwan Delage; Samuel Chaffron; et al. (Nature Communications)
Abstract Diatoms constitute one of the most diverse and ecologically important phytoplankton groups, yet their large-scale diversity patterns and drivers of abundance are unclear due to limited observations. Here, we utilize Tara Oceans molecular and morphological data, spanning pole to pole, to describe marine diatom diversity, abundance, and environmental adaptation and acclimation strategies. The dominance of diatoms among phytoplankton in terms of relative abundance and diversity is confirmed, and the most prevalent genera are Chaetoceros, Thalassiosira, Actinocyclus and Pseudo-nitzschia. We define 25 distinct diatom communities with varying environmental preferences illustrative of different life strategies. The Arctic Ocean stands out as a diatom hotspot with 6 of the diatom communities being exclusive to it. Light harvesting and photoprotection are among the cellular functions in which natural diatom populations invest the bulk of their transcriptional efforts. This comprehensive study sheds light on marine diatom distributions, offering insights to assess impacts of global change and oceanic anthropogenic impacts.